GREEN SYNTHESIS OF SILVER NANOPARTICLES: ITS EFFECT ON QUORUM SENSING INHIBITION OF URINARY TRACT INFECTION PATHOGENS - Sheikh, Shaheen; Tale, Vidya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study was conducted to evaluate the antimicrobial and anti-quorum sensing (QS) ability of nanoparticles synthesized using fruit wastes. Methods: QS is a system of response and stimuli correlated to population density. Bacteria by QS secrete certain signaling molecules called autoinducers. These bacteria also have a receptor that can specifically detect the signaling molecule known as an inducer. Since QS governs numerous processes in bacteria including virulence, QS inhibition promises to be an ideal target for the development of novel therapeutics. In the present study, silver nanoparticles (AgNPs) synthesized from the ginger, lemon peel, cinnamon, corn silk, pomegranate peel, and orange peel exhibited anti-QS properties by inhibiting violacein production in Chromobacterium violaceum assayed using agar well diffusion method. Results: AgNPs were synthesized from various cost-effective fruit waste sources. These AgNPs exhibited significant antibacterial and anti-QS properties. Conclusion: Hence, such sources can be explored for developing the effective therapy for urinary tract infections. Â 